1972
DOI: 10.1002/macp.1972.021520124
|View full text |Cite
|
Sign up to set email alerts
|

A study of intramolecular reaction during linear polyurethane formation

Abstract: Eingegangen a m 6. Mai 1971) S U M M A R Y :The numbers of rings formed in the reactions of hexamethytenc diisocyanate with two polyethylene glycols have been determined as a function of dilution and ratios of reactants. I n this work the cryoscopic apparatus developed in the preceding paper has been utilised. It is found that more rings are formed (a) in dilute solutions, (b) with reactants of lower molecular weight, and (c) in reactions at equimolar concentrations. Some of the results may be interpreted appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 10 publications
5
54
1
Order By: Relevance
“…Such a differentiation and characterization is useful for any kind of chemical reaction and it came into play for step-growth polymerizations when Jacobson and Stockmayer [78,79] published their studies of ring-chain equilibria and ring-formation by back-biting degradation. About thirty years ago a computer-supported speculative simulation of irreversible step-growth kinetics let Stepto et al [80,81] and Gordon and Temple [82,83] conclude that at least at low or moderate concentrations cyclization competes with each growing step. However, the lack of experimental evidence hindered a broader acceptance of this new polycondensation theory by the international community of polymer chemistry.…”
Section: The Role Of Cyclizationmentioning
confidence: 99%
“…Such a differentiation and characterization is useful for any kind of chemical reaction and it came into play for step-growth polymerizations when Jacobson and Stockmayer [78,79] published their studies of ring-chain equilibria and ring-formation by back-biting degradation. About thirty years ago a computer-supported speculative simulation of irreversible step-growth kinetics let Stepto et al [80,81] and Gordon and Temple [82,83] conclude that at least at low or moderate concentrations cyclization competes with each growing step. However, the lack of experimental evidence hindered a broader acceptance of this new polycondensation theory by the international community of polymer chemistry.…”
Section: The Role Of Cyclizationmentioning
confidence: 99%
“…Cex t Cex t ' N However, if this assumption is not equation [7] can be rearranged to give [12] made,…”
Section: An Examination Of the Frisch And Kilb Theories Of Gelation Wmentioning
confidence: 99%
“…In addition, measured values of a~ are always greater (2)(3)(4)(5)(7)(8)(9)(10) than the value of 0c-1) -1 predicted by equation [1]. The measurement of pre-gel intramolecular reaction (11) as N~, the number fraction of ring structures at given extents of reaction, is difficult experimentally (11,12), but the measurement of a c is relatively simple (13), and most of the experimental data available on pre-get intramolecular reaction relate to a c.…”
mentioning
confidence: 94%
“…Further studies in this direction were summarized in two review articles. [9,10] Between 1970 and 1980 Stepto and coworkers, [11,12] and Gordon and coworkers [13,14] conducted speculative calculations of the kinetics of step-growth polymerizations assuming that cyclization competes with each chain-growth step. Those authors also concluded that 100% conversion should yield 100% of cyclic reaction products.…”
Section: Introductionmentioning
confidence: 99%